2010
DOI: 10.1182/blood-2010-05-283739
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identifies novel loci for plasma levels of protein C: the ARIC study

Abstract: Protein C is an important endogenous anticoagulant in hemostasis. Deficiencies of protein C due to genetic mutations or a low level of circulating protein C increase the risk of venous thromboembolism. We performed a genome-wide association scan for plasma protein C antigen concentration with approximately 2.5 million single-nucleotide polymorphisms in 8048 individuals of European ancestry and a replication analysis in a separate sample of 1376 individuals in the Atherosclerosis Risk in Communities Study. Four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
85
4

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(100 citation statements)
references
References 32 publications
11
85
4
Order By: Relevance
“…This association has been widely replicated in additional studies and populations (40)(41)(42). Further genome-wide analyses have documented associations of this region with risk of type 2 diabetes (T2D), total cholesterol, fasting insulin, C peptide, homeostasis model assessment of insulin resistance (HOMA-IR), and concentrations of a number of other metabolites, including C-reactive protein (CRP), mannose, the liver enzyme γ-glutamyl transferase, and urate (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Functionally, p.Pro446Leu-GKRP has been shown to decrease F6P-mediated inhibition of GCK and reduce nuclear sequestration of GCK (13,43).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…This association has been widely replicated in additional studies and populations (40)(41)(42). Further genome-wide analyses have documented associations of this region with risk of type 2 diabetes (T2D), total cholesterol, fasting insulin, C peptide, homeostasis model assessment of insulin resistance (HOMA-IR), and concentrations of a number of other metabolites, including C-reactive protein (CRP), mannose, the liver enzyme γ-glutamyl transferase, and urate (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Functionally, p.Pro446Leu-GKRP has been shown to decrease F6P-mediated inhibition of GCK and reduce nuclear sequestration of GCK (13,43).…”
Section: Introductionmentioning
confidence: 92%
“…Given its central role in hepatic glucose metabolism, it is probably not surprising that GCKR has emerged as an important locus for susceptibility to diabetes and related traits (12,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). GWAS initially identified a 400-kb region on chromosome 2 significantly associated with serum triglycerides (28).…”
Section: Introductionmentioning
confidence: 99%
“…In a GWAS of plasma levels of PC including more than 8000 participants, the strongest association was observed at the PROCR locus, and the rs867186 polymorphism explained an estimated 10.4% of the variance in PC. 51 In 2 studies included in the systematic review that measured prothrombin (fragment 1 and 2) levels relative to genotype, a significant increase was seen for those with the G allele. 17,18 The G allele was also associated with elevated levels of FVII and FVIIa in a study of approximately 2000 healthy middle-aged men.…”
Section: Vtementioning
confidence: 99%
“…Although we do not discuss the results in this review, GWAS for coagulation and fibrinolysis have also been reported. [81][82][83][84][85] Associations at 12q24 Given the close biological relationship between PLT and CAD, 3 Soranzo et al 28 evaluated the risks of CAD in the loci associated with PLT and found an overlap between these two traits at 12q24. The variants identified at 12q24 were encompassed by a long-range haplotype that extended 41.5 Mbps on which significant pressure of natural selection was observed.…”
Section: Genetic Factors For Pltmentioning
confidence: 99%